Alat Pemantau dan Penghitung Jumlah Pengunjung Berbasis Aplikasi Telegram - Rindang Alamsyah; Ika Karlina Laila Nur Suciningtyas; Nanta Fakih Prebianto; Iman Fahruzi; Imam Sholihuddin; Abdurahman Dwijotomo; Lalu Kaisar Wisnu Kita; Indra Daulay (Journal of Applied Electrical Engineering, 2023)
A visitor monitoring and counting device is a tool designed to send information in the form of images and the number of visitors detected through a camera and sensors installed on the device. This device is based on the Telegram application using the ESP32-CAM module as the camera to capture images of each incoming visitor. The device is equipped with an infrared sensor used to detect incoming visitors. The device works by counting the number of visitors when they enter, and then sending a signal to the ESP32-CAM to capture a physical image as evidence. The data from the device's operation is sent through the Telegram application. The research results show that the device functions well at a distance of 60 cm, but it does not function properly at a distance of 90 cm. The average time required for the device to send an image to the application is 2.5 seconds. The fastest time required by the system to read data between one visitor and the next is 15,4 seconds.